Dalihan na tolu sebagai teologi lokal:: Memahami falsafah dalihan na tolu dan Lukas 16: 19-31 dari perspektif Robert J. Schreiter - Jhon Ferdinand Sihombing; Claudie Valda Silooy (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
This paper aims to discuss the argument of na tolu in Batak Toba and Luke 16:19-31 with Robert J. Schreiter's perspective on local theology. Preliminary studies of dalihan na tolu pretext have revealed the fact that there are differences between one person and another due to hula-hula status, dongan tubu or boru. The hula-hula will be highly respected in a ritual, dongan tubu as a friend of the person who holds the ritual, while the boru is the workers in the ritual. In this case, hula-hula becomes the party who really benefits compared to boru. In reviewing this paper, the author will use a qualitative method, namely Robert J. Schreiter's theology-based contextualization efforts on local theology with literature review. This study finds that dalihan na tolu pretext upholds the very high value of kinship, as well as Luke 16:19-31 which emphasizes caring for others. Based on this study, the authors conclude that the teaching of values contained in dalihan na tolu is a message that has theological value and is very important to defend.